Removal of Cholesterol by b-Cyclodextrin - Jiang, Huiming; Zhang, Shufen; Shi, Qi (Asian Journal of Chemistry, 2011)
This paper reviews cholesterol removal methods by b-cyclodextrin or its derivatives. Cholesterol was complexed by b-cyclodextrin or its derivatives in two major ways i.e., molecular imprinting and direct inclusion. It revealed that b-cyclodextrin dimers linked via different bridges exhibited much higher binding capability than b-cyclodextrin itself, of which, a b-cyclodextrin dimer linked by a thioether bridge exhibits the highest binding constant with cholesterol, which reaches up to (3.30 ± 0.80) × 106.